Synergistic effect of low handgrip strength and malnutrition on 4-year all-cause mortality in older males: A prospective longitudinal cohort study. (July 2019) - Wang, Yu-Chun; Liang, Chih-Kuang; Hsu, Ying-Hsin; Peng, Li-Ning; Chu, Che-Sheng; Liao, Mei-Chen; Shen, Hsiu-Chu; Chou, Ming-Yueh; Lin, Yu-Te
Highlights: Malnutrition was associated with low handgrip strength among older male adults. Both malnutrition and low handgrip strength were predictors for mortality. Low handgrip strength with malnutrition synergistically increased the mortality risk. Abstract: Background: No studies have yet examined the interrelationship of malnutrition and low handgrip strength in terms of mortality. The aim of the present study was to evaluate the potential synergistic effects of malnutrition and low handgrip strength on mortality among older adults living in a retirement community. Methods: This prospective longitudinal cohort study recruited subjects aged 65 years and over from a veterans care home in Taiwan in 2013. Nutritional status was assessed using the Mini-Nutritional Assessment-Short Form (MNA-SF, malnutrition was MNA-SF<12); muscle strength was measured by handgrip strength (low handgrip strength was handgrip strength <26 kg). The Kaplan-Meier method with the log-rank test was used to estimate survival differences between groups and Cox proportional regression model was used to estimate the adjusted difference in 4-year all-cause mortality between groups. Results: Recruited for the present study were 333 male participants (mean age 85.4 ± 5.7 years). Of these, 50.2% had malnutrition and 54.7% had low handgrip strength. Compared with subjects with no malnutrition and low handgrip strength, those with malnutrition had significantly greater risk of 4-year all-cause mortality (adjusted hazards ratio: 2.05, 95% confident interval [CI]: 1.04–4.01); hazard ratio increased to 3.41 (95% CI 1.93–6.04) for those with both malnutrition and low handgrip strength. Conclusions: Malnutrition was an independent risk factor for 4-year all-cause mortality and low handgrip strength with malnutrition synergistically increased the mortality risk. Further study is needed to confirm the effectiveness of integrated programs to assist those at risk.